Reconciling the value of Schottky barriers in small molecular organic photovoltaics from J-V and C-V measurements at low temperatures towards the estimation of open circuit voltage at 0 K - Biring S.; Sung Y.-M.; Nguyen T.P.; Li Y.-Z.; Lee C.-C.; Yi Chan A.H.; Pal B.; Sen S.; Liu S.-W.; Wong K.-T. (My University, 2025)
Open circuit voltage of a photovoltaic system, in general, is constrained by the Schottky barrier (SB) heights formed at the electrodes. Here, the SB heights which are inhomogeneous in nature at the anode-semiconductor junction of a donor-acceptor-acceptor molecule, 2-[(7-(4-[N,N-bis(4-methylphenyl)amino]phenyl)-2,1,3-benzothia-diazol-4-yl)methylene] propane-dinitrile (DTDCPB), mixed with C70 as a bulk heterojunction have been studied thoroughly by inserting an insulating layer of MoO3 with different thicknesses (6 nm, 12 nm, 18 nm) and measuring the current density-voltage (J-V) and capacitance-voltage (C–V) characteristics of the photovoltaics under a large temperature range of 100K–300 K for proper estimation of open circuit voltage (Voc). Experimental results reveal a linear inverse temperature dependence of SB heights in the whole temperature range. The mismatch in the extracted values of SB heights from the independent measurements of J-V and C–V vanishes under the consideration of non-linear temperature dependence of built-in potential (Vbi) leading to the legitimate prediction of Voc. © 2019 Elsevier B.V.